Respuesta :

Answer:

(0,6),(-2,0)

Step-by-step explanation:

The given equation are;

[tex]y=x^2+5x+6[/tex]

and

[tex]y=3x+6[/tex]

We equate both equations to get;

[tex]x^2+5x+6=3x+6[/tex]

Regroup all terms on the left hand side to obtain;

[tex]x^2+5x-3x+6-6=0[/tex]

[tex]x^2+2x=0[/tex]

Factor;

[tex]x(x+2)=0[/tex]

[tex]x=0,x+2=0[/tex]

[tex]x=0,x=-2[/tex]

We can put the values of x into any of equations preferably the linear equation to get;

[tex]y=3(0)+6=6[/tex], when x=0.

and

[tex]y=3(-2)+6=0[/tex], when x=-2.

The solutions are

(0,6),(-2,0)

ACCESS MORE